Sentinel lymph nodes biopsy for malignant tumors using Technefit radioactive colloid Technetium 99mTc - Irina Onofriychuk; Aziz Zikiryahodzhaev; Anatoliy Ermakov; Nataliya Ablitsova; Eric Saribekyan; Elena Rasskazova; Gadgimurad Zapirov; Stanislav Mikhailov; Andrey Kaprin; Anna Sukhotko; Serghei Covantsev (Folia Medica)
Introduction: Technetium-99m (99mTc) is a short-lived nanocolloid nuclide widely used by oncologists to diagnose and identify cancer dissemination. Aim: The aim of the current study was to develop the technique of radiopharmaceutical preparation (RPP) of Technefit99mTc aimed at examining sentinel lymph nodes (SLN) before surgery. Materials and methods: We performed a series of trials (33 patients). Based on the information obtained from the portable gamma detector NEO2000 during surgery, a biopsy of the sentinel lymph nodes was carried out when RPP Technefit 99mTc accumulated in a specific lymph node. Results: We determined maximum activities, volume, and peculiarities of administration of radioactive colloid Technefit99mTc in order to examine and perform the biopsy of SLN in the patients with malignant tumors. The most informative results in terms of scintigraphy images of sentinel lymph nodes were revealed in the first trial of the research, with all 5 cases (100%) showing positive results. The first trial included Technefit intradermal-hypodermal injection into one point above the tumor node, RPP activity of 75 to 200 mBq at a room temperature of 21°C, without preliminary anesthesia with Novocain solution. Conclusion: We determined the most efficient dosages of activities, volume, and characteristics of radioactive colloid administration aimed at the examination and biopsy of sentinel lymph nodes using the radiopharmaceutical preparation Technefit 99mTc in patients with malignant tumors of different localizations, namely breast cancer and skin melanoma. In some cases, we did not find any signs of considerable lowering of the Technefit 99mTc activity, which shows that there is a very slow filtration of Technefit 99mTc through the pores of lymph capillaries.